1995
DOI: 10.1104/pp.108.4.1623
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Pyruvate Dehydrogenase (Molecular Cloning of the E1[alpha] Subunit and Expression Analysis)

Abstract: The mtPDC occupies a central point in cellular energy metabolism, linking glycolytic carbon metabolism with the citric acid cycle. Since the reaction catalyzed by mtPDC is irreversible, this represents the committed step of carbon entry into the citric acid cycle. Plants are unique in that, in addition to mtPDC, they contain a second isoform of PDC localized in plastids. This isoform is believed to be involved in the provision of acetyl-COA for fatty acid, isoprenoid, and amino acid biosynthesis (Camp and Rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…A similar pattern was observed in an earlier study of the phosphorylation state of mtPDC in pea seedlings [51]. As was found with the plPDC subunits, mtPDC is highly expressed in pollen [52,53].…”
Section: Expression Of Mtpdcsupporting
confidence: 84%
“…A similar pattern was observed in an earlier study of the phosphorylation state of mtPDC in pea seedlings [51]. As was found with the plPDC subunits, mtPDC is highly expressed in pollen [52,53].…”
Section: Expression Of Mtpdcsupporting
confidence: 84%
“…The N-terminal amino acid sequences of the 43 and 41 kDa proteins were identical and matched a sequence beginning 27 residues from the start codon of a predicted amino acid sequence derived from a full-length cDNA clone (accession number GB Z26949) encoding E1α of mPDC from potato [12]. It is not clear whether the 43 and 41 kDa proteins in the purified potato mPDC represent isoenzymes of E1α, the products of C-terminal proteolysis of a single polypeptide or differential post-transcriptional processing products.…”
Section: Protein Gel Electrophoresis and N-terminal Sequencing Of Potmentioning
confidence: 86%
“…Further attempts to identify the components of plant mPDC have used antibodies raised against mammalian, yeast and several plant mPDC polypeptides. The E1α component has been identified as a 41-43 kDa protein on the basis of reaction with antibodies raised against E1α from mammals, yeast and Zea mays [11][12][13] and on the basis of phosphorylation studies [14,15]. Using anti-(pig mPDC E3) antibodies the E3 component in pea mitochondria had been identified as a 58 kDa protein [1] or a 67 kDa [11] protein.…”
Section: Introductionmentioning
confidence: 99%
“…Grof et al (1995) studied the development of the E1␣-subunit of pyruvate dehydrogenase during cucumber seedling development. It has been shown that this subunit undergoes lightdependent inactivation by phosphorylation to potentially limit the activity of the TCA cycle during photorespiration (Gemel and Randall, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that new carbon fixation by photosynthesis is required for full TCA cycle activity. Recently, it was suggested that the TCA cycle may be limited postgerminatively by transcriptional control of mitochondrial pyruvate dehydrogenase (Grof et al, 1995).…”
mentioning
confidence: 99%